STRATEGIC MODELING OF TRANSACTION COSTS FOR AGRICULTURAL ENTERPRISES IN THE CONTEXT OF WAR RISKS AND INSTITUTIONAL INSTABILITY - Tiutiunnyk, Svitlana; Salyha, Oleksandr (Current Problems of Sustainable Development, 2026)
The subject of this study is the process of strategic modeling of transaction costs for agricultural enterprises in the context of war-related risks and institutional instability. The purpose of this article is to develop a comprehensive model of a hierarchical structure for adaptive cost management that enables the conversion of accounting data into strategic decisions to strengthen the competitiveness of agribusiness. The article argues that the modern logistics system in the agricultural sector operates under conditions of transaction costs, where macroeconomic shocks are progressively translated into specific micro-costs for enterprises. The authors propose a multi-level cost structure that reveals the hierarchical relationship between institutional instability and the increase in transaction costs. It has been demonstrated that the unique nature of agricultural assets in wartime acts as a catalyst for losses, necessitating a reevaluation of basic management models. The scientific novelty of this work lies in the formalization of military impacts through a system of mathematical indicators. A model for minimizing aggregate costs has been developed, incorporating a military risk coefficient (Rwar) and an institutional instability index (Iinst). The use of the «Innovation Offset» parameter is proposed to assess the effectiveness of digitalization as a tool for mitigating external shocks. To measure a company’s resilience, the «Transactional Strength» (Kts) indicator has been introduced, which allows for an assessment of the business model’s ability to adapt to extreme environmental conditions. The practical significance of the results lies in the creation of a combined «Accounting–Risk–Decision» model that operates on the principle of a closed-loop feedback system. A strategic choice matrix has been developed, offering differentiated scenarios (optimization, digitalization, vertical integration based on the Make-or-Buy dilemma, or relocation) depending on the criticality of external factors. The proposed mechanism enables agricultural enterprises to transition to a «management by exception» model, minimizing the time lag between the emergence of a military threat and the implementation of a management plan.
Keywords: transaction costs; agricultural enterprises; war risks; institutional instability; strategic modeling; digitalization; transaction resilience